Understanding obesity: genes and environment in the determination of body weight - Leibel, Rudy (Henry Stewart Talks, 2007)
Evolutionary arguments for regulation of body fat, Gene x gene x environment interactions, Molecular physiology of control of body weight, Human monogenic obesities, Complex genetics of human obesity, Threshold model for control of body weight, Bioenergetics of reduced body weight, Structural plasticity in the CNS systems regulating body fat